Capital Outlay as an Educational Equity Issue: A Review of Educational Research and Legal Opinion - David C. Thompson; William E. Camp; G. Kent Stewart (Journal of Research in Rural Education, 1988)
This paper examines the issue of how school districts have financed facility needs and notes that numerous recent legal decisions address capital outlay as an equity issue. The decisions are reviewed and implications for educational policy makers are discussed